Valoration of the Araticum (Annona crassiflora Mart.) (Research, Society and Development, 2022)
The Araticum (Annona crassiflora Mart.), is a typical fruit tree from Cerrado and has its harvest period between february and april. The fruit is covered by a brown peel, very thick, and contains numerous black and smooth seeds attached to the pulp. It is consumed naturally, but the pulp is also widely used in juices, ice cream and candies. The present study aims to economically value the Araticum through the willingness to pay (DAP) of the interviewees. Therefore, the tool used was the Contingent Assessment Method, which consists of pricing the economic value of environmental assets through the application of questionnaires. The initial sample contained 155 peoples, of both genders, who were asked if they knew or not the Araticum. Of these, 131 knew the fruit (84.5%) and 24 did not (15.5%). Only the participants who recognized the fruit continued with the questionnaire, answering socioeconomic and marketing questions, such as the willingness to pay (DAP) for each araticum fruit. The estimated mean DAP was R$ 1,22 per raw fruit.